Dispersion of carbon black in epoxy resin and the electrical property of the nanocomposite - Mailabari, R.J. (Asian Research Publishing Network, 2016)
The enhanced property of nanocomposite depends largely on the physical property of the dispersed nanoparticle and the state of dispersion of the nanoparticle, a well-dispersed structure generally results in additional enviable nanocomposite properties. In this paper, the carbon black nanoparticles were characterised using XRD, SEM, FESEM, TEM and SAP/BET techniques to establish the morphology and other physical properties of the particle. The CB nanoparticles were dispersed in epoxy resin using a combination of different dispersion techniques to obtain an epoxy resin nanocomposite with a network of carbon black conducting particle. The electrical properties of the nanocomposite were measured with respect to the wt loading of CB and the percolation threshold was found to be 20 - 25 wt of CB. The electrical resistivity of the nanocomposite was found to be influenced by the size of the nanoparticles, morphology and the loading content of the CB nanoparticles. Â©2006-2016 Asian Research Publishing Network (ARPN).